Microchip Bags and Waste Sorting - Matteo Picchio (Global Labor Organization (GLO), 2021)
We evaluate the effectiveness of placing microchips on the bags for the curbside collection in reducing the unsorted urban solid waste and increasing the fraction recycled. The microchip allows the waste collection company to identify the users that left the bags on the curb and check whether they properly sorted the waste. Our study is carried out in the Italian province of Macerata (Marche, Italy), where the bag microchips were introduced only in some municipalities in 2013. Exploiting monthly information on waste collection and natural experiment methods, we find that, two years after the programme start, the bag microchip increased the fraction recycled by 3-4:5 percentage points and decreased the monthly unsorted waste by 1-2 kilograms per capita.
Keywords: C23; D78; Q53; 330; Recycling behaviour; unsorted waste; microchip bags; natural experiment; difference-in-differences; synthetic control method